Usulan Perubahan Tata Letak Fasilitas Produksi UMKM IBS Menggunakan Metode ARC dan ARD - Daffa Aqilah Nanda Nugraha; Hidayat Hidayat; Yanuar Pandu Negoro (G-Tech: Jurnal Teknologi Terapan, 2024)
MSME IBS is a home industry that produces baby sofas, baby bedding, etc. MSME IBS faces material handling problems due to poor layout management factors, as well as the realization of the amount of production that does not reach the predetermined target. The research aims to solve the problem of poor layout to be better using the ARC and ARD methods. The resulting efficiency is 49% with a distance of 1512,5m resulting in a decrease of 51% from 100% of the initial distance with a distance of 3085m after making changes from the initial layout to the proposed layout. For this reason, it requires facility improvements to reduce the distance traveled and the accumulation of goods that make the production flow narrow and far by applying the proposed layout between production rooms in order to reduce material handling.